Identifying energy solutions to support development of irrigated agriculture in Ethiopia - Xie, Hua; Mekonnen, Dawit Kelemework (Applied Research Programme on Energy and Economic Growth, 2022)
Sub-Saharan African countries have long been beset with energy poverty. While there are already many studies on how to improve access to modern energy services in the region, those energy planning analyses are dominated by residential energy demand, and not much attention has yet been paid to the productive use of energy in agriculture. This paper aims at filling this knowledge gap by presenting a country-level planning analysis in Ethiopia to inform investment decisions and policy discussions about the promotion of energy use in agriculture to support the development of irrigated agriculture in the country. Irrigation is considered as a promising option to boost agricultural production and enhance agricultural resilience in Ethiopia. However, the strong water-energy nexus in irrigated agriculture implies that irrigation development in Ethiopia is hampered by energy poverty. The challenging aspect of the planning analysis for productive use of energy in irrigated agriculture is that, in addition to access to energy, irrigation adoption is constrained by many other factors such as availability of water resources, land suitability, and market potential of irrigated crops. In this study, we put the analysis into an integrated irrigation-energy planning framework and used the integrated modelling approach to identify groundwater irrigation development potentials in Ethiopia under three energy solutions: grid-connected electricity, off-grid solar PV, and diesel energy The analysis shows that by 2030, there is a potential to add about 1.05 million hectares of groundwater irrigated area. Both on-grid and off-grid energy solutions will play an important role in the effort to develop groundwater-based irrigated agriculture in Ethiopia. Moreover, the application potential of the two off grid energy solutions(solar PV and diesel) critically depends on the energy pricing policy of the country. A reform that removes the subsidies on fossil fuels will help promote the use of solar PV powered irrigation system significantly. Finally, Ethiopia is a country rich in renewable energy resources. Apart from solar energy, other sources of renewable energy available in Ethiopia include wind, geothermal, and micro-hydrology. There is also keen interest in investing in mini-grids. The approach developed in this study can be extended to accommodate these energy solutions, and this constitutes a topic that invites future research.